MISKONSEPSI SISWA PADA MATERI PECAHAN DI KELAS VIII SMP LKIA PONTIANAK - Hakim, Maida Sujana; Yani T, Halini; Yani T, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aims of this study is to describe the misconceptions experienced by the students and the causes on the material of pure fraction count operation and mixed fractions in class VIII SMP LKIA Pontianak. The research method used is descriptive with case study research. Subjects in this study amounted to 6 students of grade VIII SMP LKIA Pontianak who experienced misconception on the fractional material. The data collection tools used are multiple choice questions, and interviews. Test questions are given to explore whether misconceptions are occurring, and interviews are conducted to extract information from students as a whole and in depth based on student test results. The results of this study indicate misconceptions experienced by students are misperception of generalization, misconception of notation, and misconception of calculation. The causes of misconceptions experienced by students are caused by: 1) incomplete understanding such as incomplete records; 2) the student's own thinking is like a student's thinking which assumes that the sum of the fractions is equal to the sum of integers, the student's thinking which assumes that the sum of integers is the same as the multiplication of fractional numbers, the student's thinking which assumes that there is no sign.Keywords: Misconception, Fraction.